Anesthetic Management in Atrial Septal Defect with Small Left Ventricle and Pulmonary Hypertension - Christina, Angela; Hidayat, Jefferson (Writing Center IMERI FMUI, 2024)
Atrial septal defect (ASD) can remain undiagnosed throughout adulthood and frequently develop complications. We report major challenges caused by late onset ASD including small left ventricle and pulmonary hypertension. We report the successful management of ASD closure in a 24-year-old man presented with a large secundum ASD with a diameter of 57 mm and bidirectional shunt, and a small left ventricle (LV). Moderate mitral regurgitation (MR) and tricuspid regurgitation (TR) were also found. Right heart catheterization showed high flow, low resistance pulmonary hypertension (PH). Despite surgery went well with short period of cardiopulmonary bypass (CPB) time. We found decreased function in both ventricles when weaning from cardiopulmonary bypass machine, which required epinephrine 0.2-0.4 mcg/kg/min, milrinone 0.375 mcg/kg/min, norepinephrine 0.05 mcg/kg/min, and dobutamine 5 mcg/kg/min to stabilize the hemodynamics. Post-operative transesophageal echocardiography (TEE) showed a left to right shunt small ASD with a diameter of 2 mm, trivial TR, moderate MR, no LV D-Shape, and small LV. The ejection fraction was 59%, with a high level of hemodynamic support, cardiac output of 3.6 l/m, and stroke volume of 41 mL. The patient was able to be weaned off hemodynamics supports and ventilator within five days. The patient was discharged 12 days after surgery. The management of ASD can be challenging in the presence of small LV, pulmonary hypertension, and arrhythmia.